1992
DOI: 10.1192/bjp.160.4.570
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluoxetine in heroin addiction

Abstract: for medical science (Engel, 1980), and our Patron has drawn attention to potentially additional dimensions of spiritual, ecological, and perhaps even political influences on the human psyche and its manifes tations. The variety and complexity of these influences is a source ofboth wonder and frustration;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In addition, two research groups have reported that fluoxetine substantially reduces heroin craving in human addicts (Gerra et al 1995;Maremmani et al 1992). These studies, together with the current findings, indicate that enhancing 5-HT transmission in opiate experienced subjects may decrease the desire for morphine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two research groups have reported that fluoxetine substantially reduces heroin craving in human addicts (Gerra et al 1995;Maremmani et al 1992). These studies, together with the current findings, indicate that enhancing 5-HT transmission in opiate experienced subjects may decrease the desire for morphine.…”
Section: Discussionmentioning
confidence: 99%
“…They show a satisfactory retention rate compared with uncomplicated SUD patients or non-bipolar SUD patients. The use of fluoxetine as the add-on to naltrexone maintenance has been shown to improve patients’ outcomes, suggesting that naltrexone has an anti-reward property, that is specifically reversible through fluoxetine’s antidepressant effects [63,64].…”
Section: Treatment Of Mood Disorders During Mmtmentioning
confidence: 99%
“…As methadone and buprenorphine are used for the maintenance of heroin addicts, they can be associated with many other drugs, especially selective serotonin reuptake inhibitors (SSRI) such as fluoxetine or fluvoxamine. It has previously been shown that these drugs are useful in the treatment of drug craving [25]. Indeed, depression is a risk factor for illicit drug-taking relapse and for failure of maintenance therapy among opioid addicts [21].…”
mentioning
confidence: 99%